Artficial Intelligence and Creative Worker In Indonesia: The Double Edge Sword Effect - Daini Unifianto Fauzi; Riani Rachmawati (Institute of Multidisciplinary Research and Community Service, 2026)
The increasing adoption of artificial intelligence (AI) in the workplace has raised concerns about its implications for employees, particularly creative workers, who are considered vulnerable to technological disruption. This study aimed to examine the influence of AI awareness on individual work performance, mediated by job insecurity and work engagement, among creative workers in Indonesia. A quantitative approach was employed through a cross-sectional survey of 227 creative workers from various creative occupations in Indonesia using a structured questionnaire. Data were analyzed using Structural Equation Modeling (SEM) with LISREL version 8.80 to examine both direct and indirect relationships among the proposed variables. The findings revealed that AI awareness positively affected job insecurity (β = 0.62, t = 7.95) and work engagement (β = 0.23, t = 2.42), while job insecurity negatively influenced work engagement (β = −0.26, t = −2.81). Furthermore, work engagement positively affected individual work performance (β = 0.72, t = 7.56). Work engagement significantly mediated the relationship between AI awareness and individual work performance (t = 2.21), whereas job insecurity significantly mediated the relationship between AI awareness and work engagement (t = −2.03). However, the serial mediating effect of job insecurity and work engagement on the relationship between AI awareness and individual work performance was not significant (t = −1.95). These findings indicate that creative workers perceive AI as a double-edged phenomenon: although it raises concerns regarding job continuity, it may also stimulate engagement that supports performance. By integrating the STARA awareness framework and the Job Demands–Resources theory, this study contributes to the current body of research on employees' psychological responses to AI-driven transformation. It offers practical insights to help organizations foster adaptive attitudes toward AI while maintaining employee engagement and performance amid ongoing technological transformation. Keywords: AI awareness; Job insecurity; Work engagement; Individual work performance; Creative workers.